Commentaries on Public Consultation Paper (No. 1/2019): The Proposed Regulatory Framework for the Issuance of Digital Assets through Initial Coin Offerings (ICOs) - Mohd. Nor, Rizal; Mohd. Zain, Nor Razinah; Abdullah, Adam; Khurshid, Usman (2019)
This paper is written to provide the commentaries for the Public Consultation Paper (No.1/2019) or CP on the Proposed regulatory framework for the issuance of digital assets through initial coin offerings (ICOs). The CP was issued by the Securities Commission of Malaysia or SC dated on 6th of March 2019. This paper will be known as CCP onwards. This is important to ensure the smoothness of explanation and its proper identification.